1970
DOI: 10.1002/1097-0142(197008)26:2<368::aid-cncr2820260219>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Mucoepidermoid carcinoma of salivary gland origin.Classification, clinical-pathologic correlation, and results of treatment

Abstract: Sixty patients with mucoepidermoid carcinoma of salivary gland origin were studied. The pathologic findings and the clinical course were examined separately and then correlated. The tumors are classified as either well, moderately, or poorly differentiated. The criteria used to classify the lesions are discussed, and pathologic features are illustrated. The most important factors in the prognosis are: 1. degree of histologic differentiation, and 2. presence or absence of tumor on the lines of surgical excision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1
8

Year Published

1976
1976
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(71 citation statements)
references
References 6 publications
1
60
1
8
Order By: Relevance
“…The modified Healey system is based on certain qualitative histological parameters. 14,15 In our study, we applied AFIP grading system and nine out of 13 MEC were reported as low grade, three cases as high grade and one case as intermediate grade. In the three cases of MEC of high grade, the consistent features were minimal intracystic component, presence of cellular atypia, necrosis and invasion by nests of tumour cell and they would be designated as high grade lesions in both AFIP and Brandwein systems.…”
Section: Mucoepidermoid Carcinomamentioning
confidence: 87%
“…The modified Healey system is based on certain qualitative histological parameters. 14,15 In our study, we applied AFIP grading system and nine out of 13 MEC were reported as low grade, three cases as high grade and one case as intermediate grade. In the three cases of MEC of high grade, the consistent features were minimal intracystic component, presence of cellular atypia, necrosis and invasion by nests of tumour cell and they would be designated as high grade lesions in both AFIP and Brandwein systems.…”
Section: Mucoepidermoid Carcinomamentioning
confidence: 87%
“…The clinical behavior of MEC has proved to be difficult to predict but correlations to tumor grade and stage have been reported [30][31][32][33].The histologic features that are most useful in predicting the aggressive nature of these tumors are: 1) a minor cystic component (less than 20%); 2) tumor necrosis; 3) neural invasion; 4) cellular anaplasia; and 5) brisk mitotic activity [29]. Based on the presence or absence of these features and the clinical behavior, MEC are classified as low, intermediate, and high grade.…”
Section: Mucoepidermoid Carcinomamentioning
confidence: 99%
“…The grading of MEC has evolved from a two-tiered system to a three-tiered system (6,(20)(21)(22)(23)(24).…”
Section: Mucoepidermoid Carcinomamentioning
confidence: 99%